PENYELESAIAN SENGKETA PERBATASAN DAERAH MELALUI PENGUJIAN UNDANG-UNDANG TERHADAP UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 OLEH MAHKAMAH KONSTITUSI - Erlando, Topan Rezki; Haryono, Dodi; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Since regional outonomy era, the local boundary has meaning which is important as boundary of local government authority in implementing the government function in a certain areas which is regulated by regulations and has implication to appear the conflict of interregional about affirmation of area border because it’s related to uphold existence and the sovereignty on each local governments. But originally, the process of dispute resolution has regulated in Permendagri Nomor 76 Tahun 2016 which solves the conflict through administration route, it doesn’t solve the problems, even the parties can take legal effort in constitutional court justice in this process of dispute resolution so that changed the conflict patterns which initially among a region with another one become a region with state institutions. In this research, the writing purpose is not just to describe the conflict solution process through administration process only, but also is concerned with the solution process through judicial review against Undang-Undang Dasar Republik Indonesia Tahun 1945 by Constitutional Court.The type of this research can be classified in the type of normative law research is literature. In this normative law research, the author make the research against principles of law. Then, in this research concludes that Peraturan Menteri Dalam Negeri Nomor 76 Tahun 2012 is the true regulation which is able to solve the conflict of boundary area. Administration process which regulated in Undang-undang Nomor 23 Tahun 2014 could not solve the conflict problems of boundary area yet even though the decision was final decision but also have a legal effort as judicial review in constitutional court. The author recommends that will be formed a regulation which more have legal certainty and also engages the constitutional court in solving the conflict of boundary area, because is also about constitutionality.